Cultures of America Cuban Americans - Galvan, Raul (Marshall Cavendish Corporation, 1995)
Looks at Cuba and the reasons why people left to come to the United States; explores life in America, the importance of family and religion, and types of music, celebrations, art, food, and customs; and examines contributions made by Cuban Americans
Keywords: Ethnic Studies; Hispanic American Studies; Social Science